Modeling Problem-oriented Clinical Notes - Cillessen, F. H. J. M.; de Vries Robbé, P. F. (Methods of Information in Medicine, 2012)
Objectives: To develop a model as a starting-point for developing a problem-oriented clinical notes application as a generic component of an Electronic Health Record (EHR).Methods: We used the generic conceptualization of Weed’s problem-oriented medical record (POMR) to link progress notes to problems, and the Subjective, Objective, Assessment, Plan (SOAP) headings to classify elements of these notes. Health Level 7 (HL7) Version 3 and Unified Modeling Language (UML) were used for modeling. We looked especially at the role of Conditions and Concerns, and how to model these to document clinical reasoning.Results: We developed a generic HL7-based model for progress notes. In this model the specific clinical note has a condition as its reason. An assertion can be made about a condition. Any condition, observation or procedure can be a concern that has to be tracked. Utmost important is the relationship between constituting parts of a progress note and specially between progress notes by linking a progress note to conditions that are part of an earlier progress note. From this model a comprehensive hierarchical condition tree can be built. Several views, such as chronological, SOAP and condition-oriented, are possible. The clinical notes application is used in daily clinical practice. The model meets explicit design criteria and clinical needs.Conclusions: With the comprehensive HL7 standard it is possible to model and map progress notes using SOAP headings and POMR methodology. We have developed a generic, flexible and applicable paradigm by using acts for each assessment that refer to a condition (1), by separating conditions from concerns (2), and by an extensive use of the working list act (3).
Keywords: Electronic health records; problem-oriented medical records; health level 7